رهانات الأمن السيبراني الوطني في ظل التحول الرقمي: قراءة في التأصيل المعرفي واستراتيجية المواجهة التشريعية - دلالي، الجيلالي; بلبشير، يعقوب (كلية القانون الكويتية العالمية, 2021)
يرتبط الأمن القومي للدول في الوقت الراهن بمدى أمنها وقوة دفاعاتها السيبرانية وطنيا وإقليميا ودوليا بالقدر الذي يرتكز فيه على مدى امتلاكها لتكنولوجيا المعلومات، وقدرتها على توظيفها لحماية حدود الفضاء السيبراني الاستراتيجي؛ الأمر الذي يتطلب بالتأكيد سياسة تشريعية وأمنية شاملة ترتكز على آليات الاستباق والردع، والدعم المؤسسي واللوجيستي والتنسيق البيني أو متعدد الأطراف من أجل تأسيس منظومة شاملة للأمن السيبراني. وفي ضوء ذلك، ستتناول هذه الدراسة بالتحليل والمناقشة مدى ضرورة إعادة النظر في الاستراتيجيات الأمنية لحماية الفضاء السيبراني والأدوات القانونية والسياسية اللازمة لذلك من جهة، ومن جهة أخرى إعادة النظر في الكثير من المفاهيم التقليدية مثل: الأمن، والسيادة، والقوة، والصراع، والحرب. وتهدف هذه الدراسة إلى تحفيز إرادة الرسميين نحو تأسيس منظومة شاملة للسيبرانية في الجزائر، من خلال حزمة من الآليات التشريعية والمؤسسية لضمان مواكبة ثورة المعلومات، والإحاطة بكل مستجدات عالم السيبرانية، وفي سبيل ذلك فقد اعتمدت الدراسة على المنهج الوصفي التحليلي والمقارن. وقد خلصت الدراسة إلى أن الأمن السيبراني أصبح يشكل جزءا أساسيا من أي سياسة أمنية وطنية، وأن سوء الاستغلال المتنامي للشبكات الإلكترونية لأهداف إجرامية يؤثر سلبا على سلامة البنى التحتية للمعلومات الوطنية الحساسة لاسيما على المعلومات الشخصية والبنى التحتية الأمنية الاستراتيجية، كما انتهت إلى وجود قصور قانوني وتشريعي في معالجة تطورات الجرائم السيبرانية في بعديها الأمني والاستراتيجي. وأوصت الدراسة المشرع الجزائري بضرورة وضع منظومة وطنية شاملة لأمن الفضاء السيبراني وحمايته، وتعزيز البيئة القانونية بالأدوات اللازمة بالوقاية من الجريمة السيبرانية استباقيا، ثم بعد ذلك اعتماد آليات الردع، كما أوصت أيضا بضرورة وضع استراتيجية لنشر الوعي وبنائه لدى مختلف شرائح المجتمع، سواء من كان منهم من المستخدمين العاديين أو المهنيين أو متخذي القرار والمسؤولين عن سياسات الأمن والسلامة، مما يقتضي تأمين انسجام الأنظمة القانونية المكافحة للجرائم السيبرانية. The national security of countries at the present time is linked to the extent of their security and the strength of their cyber defenses on national, regional and international spheres, to the extent that this security is based on how far they possess information technology, and their ability to employ all this to protect the borders of their strategic cyberspace. This certainly requires a comprehensive legislative and security policy based on anticipation and deterrence mechanisms, institutional and logistical support, and inter- or multilateral coordination in order to establish a comprehensive cybersecurity system. In light of this, this study paper will analyze and discuss the extent to which it is necessary to reconsider security strategies to protect cyberspace and the necessary legal and political tools for that on the one hand, and on the other hand to reconsider many traditional concepts such as: security, sovereignty, power, conflict, and war. This study aims to stimulate the will of officials towards the establishment of a comprehensive cyber system in Algeria through a package of legislative and institutional mechanisms aimed to ensure keeping pace with the information revolution, and to take note of all developments in the cyber world. For this aim, the study relied on the descriptive analytical and comparative approach. In light of this, this study analyzes and discusses the extent to which it is necessary to reconsider security strategies to protect cyberspace and the necessary legal and political tools for that on the one hand, and on the other hand to reconsider many traditional concepts such as: security, sovereignty, power, conflict, and war. The paper also aims to stimulate the will of the officials towards the establishment of a comprehensive cyber system in Algeria, through a package of legislative and institutional mechanisms seeking to ensure keeping pace with the information revolution, and to take note of all developments in the cyber world. Therefore, the study relied on the descriptive, analytical, and comparative approach. The study concluded that cyber security has become an essential part of any national security policy, and that the growing misuse of electronic networks for criminal purposes negatively affects the integrity of sensitive national information infrastructures, especially on personal information and strategic security infrastructures. It also concluded that there are legal and legislative deficiencies in addressing the developments of cybercrimes in their security and strategic dimensions. The study recommended the Algerian legislator the need to develop a comprehensive national system for the security and protection of cyberspace, and to strengthen the legal environment with the necessary tools to proactively prevent cybercrime, and then adopt deterrence mechanisms. It also recommended the need to develop a strategy to spread and build awareness among the various segments of society, whether they are ordinary users, professionals, decision makers or persons responsible for security and safety policies, which requires ensuring the consistency of legal systems against cybercrime.
Keywords: الأمن السيبراني -- الجرائم السيبرانية -- القانون الجزائري -- الفضاء السيبراني -- الأمن القومي